Władysław Warneńczyk in the light of Jan Długosz’s Roczniki (Yearlies) - Krochmal, Jacek (Balcanica Posnaniensia. Acta et studia, 1997)
The article analyzes the image of Władysław III of Varna presented in Jan Długosz’s Annals. The author examines the way in which the chronicler shaped the figure of the young king as a man, ruler, and commander, paying particular attention to Długosz’s subjective point of view. The aim of the study is to reconstruct the king’s image in Długosz’s work and to analyze the character traits attributed to him. The author uses the text of the Annals, confronting it with the Latin original and with historiographical findings concerning the chronicler’s mentality. The article demonstrates that Długosz generally presented Władysław of Varna in a positive light, emphasizing his gentleness, generosity, religiosity, humility, and ability to cooperate with the royal council. At the same time, the chronicler noted certain flaws of the monarch, such as excessive generosity and neglect of Polish affairs. The author points out that the image of the king was subordinated to the moralizing vision of history characteristic of Długosz’s narrative. The results of the analysis indicate that the Annals portray Władysław of Varna as a young and essentially good ruler whose tragic death at Varna fits into the didactic model of medieval historiography.